Model Pembelajaran Bermain Bunga untuk Meningkatkan Prestasi Belajar PKN di SMAN 3 Bungo - Juriah . (PAKAR Pendidikan, 2021)
The improvement of learning achievement uses a learning model of playing flowers in Civics learning at SMAN 3 Bungo. This study aims to determine the increase in student learning achievement by using the learning model of playing flowers in Civics class XI IPA learning at SMAN 3 Bungo, Bungo Regency. This study uses a descriptive method with a qualitative approach. The results of research in the application of the playing flower learning model can create a fun learning process and increase the interest and motivation of students to achieve learning objectives and learning achievement. The important values ​​in the Playing Flowers model are as follows: learning becomes fun, training self-confidence, forming a sportsmanship attitude, increasing interest in learning and increasing school achievement. By paying attention to the findings of the implementation of learning in this study, it can be suggested that it be used at all levels of education and all parties who wish to study the constitution of the Republic of Indonesia. This is due to the novelty values ​​contained in the learning implementation process using the flower playing strategy. Based on the results above, it can be concluded that the use of the playing flower learning model can improve student achievement in civic education (Civics) subjects at SMAN 3 Bungo, Pelepat Ilir District, Bungo Regency.